2018
DOI: 10.1016/j.anbehav.2018.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in extended phenotype increases offspring defence despite individual variation in web structure and behaviour

Abstract: Many animals actively defend their offspring using a range of behaviours from calling and mobbing in birds, to physical grappling in crustaceans, and the expression of these behaviours positively scale with offspring value. While this role of behaviour in defence is well studied, very little is known about how other traits, specifically the structure of architectural constructions such as webs and nests, contribute to offspring defence. Additionally, although some tax a show consistent individual differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 54 publications
3
16
1
Order By: Relevance
“…We conclude that plasticity in an extended phenotype can be context dependent. Although we detected no plasticity in black widow web architecture in response to their experience of the site of prey capture, other studies have found these spiders to modify their webs in response to other factors (short‐term physiological or environmental changes) (Blackledge & Zevenbergen, ; DiRienzo & Aonuma, ; Zevenbergen et al, ). Further, orb‐web spiders do vary web architecture according to their experience of the site of prey capture (Heiling & Herberstein, ; Nakata, ).…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…We conclude that plasticity in an extended phenotype can be context dependent. Although we detected no plasticity in black widow web architecture in response to their experience of the site of prey capture, other studies have found these spiders to modify their webs in response to other factors (short‐term physiological or environmental changes) (Blackledge & Zevenbergen, ; DiRienzo & Aonuma, ; Zevenbergen et al, ). Further, orb‐web spiders do vary web architecture according to their experience of the site of prey capture (Heiling & Herberstein, ; Nakata, ).…”
Section: Discussioncontrasting
confidence: 87%
“…Alternatively, web plasticity in these spiders may follow cues other than experience of the site of prey capture. For example, the spiders might respond to differences in prey features; for example, the type of vibrations they make on the web or their behavior as they struggle to break free (Escalante, ) (and see also DiRienzo & Aonuma, ; Zevenbergen et al, ). Another possibility is that the spiders may vary web architecture when prey are less plentiful, or that they vary an aspect of web design that we did not measure (e.g., the planar extent of the sheet, which was fixed in our experiment by the size of the frames we gave them).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We cannot distinguish whether this extra nest-building effort occurred prior to female spawning, then leaving the option that females were also attracted to building behavior as a potentially honest male quality signal (Zahavi, 1975), or after spawning, when nest amendments were linked to another trait like displacement fanning (Olsson et al, 2009;Svensson & Kvarnemo, 2005). Preferred males would thus invest more in nest building as part of their brood care similar to observations in birds and spiders (DiRienzo & Aonuma, 2018;Soler, Cuervo, Møller, & DeLope, 1998).…”
Section: Females Preferred Specific Nest Types Increased Male Effomentioning
confidence: 99%
“…It also allows us to see if there is day-to-day variation in web structure, if for example certain environmental conditions consistently influence web structure for all individuals. Previous studies on among-individual consistency in web structure have been conducted in captivity (Dirienzo and Montiglio 2016; Montiglio and DiRienzo 2016; Dirienzo and Montiglio 2016 Jul; DiRienzo and Dornhaus 2017; DiRienzo and Aonuma 2018), but our study took place in the wild to assess the degree of consistency of behaviour and web structure, and how they covary with each other and with spider body size, in a natural setting. Studies in standardised laboratory settings are useful when we want to control for external factors, but studies in free-living populations help us assess the degree of consistency and correlations between traits that natural selection may be acting upon.…”
Section: Introductionmentioning
confidence: 99%